Histological assesment of low temperature epidermal tissue damage in skin graft cryopreserved with antarctic yeast isolated antifreeze peptides - Khan, Muhammad Shoaib; Abubakar, Adamu Abdul; Abdul Rahman, Mohd Basyaruddin; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Mohamad Yusof, Loqman (2015)
Sub-zero injuries in living tissue as a result of re-crystallization phenomenon is the major obstacle and complicates the application of cryopreserved tissues destined for transplantation. Understanding the freezing and thawing response of tissue against the sub-zero temperature would provide better understanding in the application of the non-toxic preservation technique of living tissues. The aim of this study was to evaluate the potential of antifreeze peptides (AFP) as a cryopreservative agent for living tissue e.g. skin. To determine the effects of cryopreservation on the tissue using AFP, type 1 AFP (peptide 1 m) was used to cryopreserve skin graft in different concentrations: 0.5, 1.0 and 2.0 mg/ml at -10°C or -20°C for 24 hrs. The histological distortions effects of the tissues were measured using a scoring system to determine the extent of freezing damage incurred in cryopreserved skin tissues. It was found that relatively less microscopic tissue damages occurred at -10°C compared to -20°C at higher AFP concentration. It is concluded that skin tissue cryopreservation could maintain comparatively better microscopic tissue integrity at -10°C using 2 mg/ml concentration of AFP type 1 as the cryopreservative agent.